Psychovigilance in diabetes - Sanjay Kalra; Komal Verma; Navneet Agrawal; Atul Dhingra (Journal of the Pakistan Medical Association, 2023)
Diabetes is associated with a myriad of mental health challenges, ranging from distress and depression to schizophrenia and substance abuse. These conditions are associated with hyperglycaemia, and also interfere with efforts to achieve good glucose control. One way in which this can be handled is by screening, early diagnosis, and timely management of mental health dysfunction and disorders. We term this action as psychovigilance. Keywords: Anxiety, depression, diabetes distress, psychosocial aspects, type 1 diabetes, type 2 diabetes